Does green gross regional domestic product accommodate environmental quality and the public's welfare? - Setyanto, Alief Rakhman; Pramasha, Raizki Rienaldi (Journal of Economics Research and Policy Studies, 2023)
The economic theory of development developed from gross domestic product to observe the development of a sustainable needed connection between environmental quality and welfare society. This research aims to review the green GRDP picture to accommodate ecological quality and the welfare of society. This research uses a descriptive method with secondary data sources from a literature study. It analyzes it in-depth about Green GRDP, which previously used Brown GRDP as a basis for analyzing regional economic growth in Lampung Province. The research results obtained at the level of green GRDP growth have had high economic consequences on the agriculture and plantations sector since environmental constraints corrected them. However, a quality environment can fulfill hope for society for a more decent life. Recommendations that can be given in this study are related to the implementation of green GRDP, potentially accommodating the well-being acquired by society from the agricultural sector and plantations to increase regional economic growth in Lampung Province.